Identifiering av fel i skogliga beståndsregister med hjälp av satellitdata - Eriksson, Jonatan (SLU/Dept. of Forest Resource Management, 2008)
This thesis has focused on the possibility to use a satellite image method developed by Metria Mijöanalys to identify stands that are wrongly registered in Holmen Skogs database. The method is only intended for identifying stand with poor descriptions in Holmen's database that needs to be updated and not for updating the stand information.